Effect of environmental and socioeconomic factors on the use of dental floss among children: a hierarchical approach - Renita Baldo MORAES; Beatriz Baldo MARQUES; Diana Maria Pigatto COCCO; Jessica Klöckner KNORST; Fernanda TOMAZONI; Thiago Machado ARDENGHI (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract The aim of this study was to evaluate the association of environmental and socioeconomic characteristics with the use of dental floss in preschool children. This cross-sectional study was conducted with a sample of 402 preschool children aged 1-5 years, from Santa Cruz do Sul, a Southern city in Brazil. Mothers answered questions about environmental, demographic, and socioeconomic characteristics. Behavior variables as use of dental floss (study outcome) and dental attendance were also evaluated. Poisson regression analysis with robust variance through a hierarchical approach was used to investigate the association of explanatory variables for use of dental floss. Prevalence ratio (PR) and 95% confidence intervals (95%CI) were estimated. The mean sample age was 3.32 years (standard deviation [SD] 1.10). Of the included children, 291 (73.12%) did not use dental floss. The environmental model indicated that children who attended daycare (PR 2.53; 95%CI 1.39-4.60) and those whose parents were members of volunteer networks (RP 1.58; 95%CI 1.02-2.46) were more likely to use dental floss. Children from families with higher income (PR 1.55; 95%CI 1.07-2.24) and maternal schooling (PR 2.21; 95%CI 1.31-3.74) presented a higher prevalence of dental floss use. Older children and those who attended dental services were also related to higher dental floss use. Our findings suggest that children who live in a supporting environment and those with a higher socioeconomic status are more likely to use dental floss.